Achieving Sustainability in Supply Chain: The Dual Role of Digital Transformation and Integration - Damar, Cyrril Ario; Nursyamsiah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the impact of Digital Transformation on sustainability performance, with supply chain integration as a mediating variable in manufacturing companies in Indonesia. This study employs a quantitative approach using purposive sampling, resulting in 215 respondents from manufacturing companies in Indonesia. Data was collected through an online survey via Google Forms and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings indicate that Digital Transformation does not directly affect sustainability performance. However, Digital Transformation positively influences Internal Integration, Supplier Integration, and Customer Integration. Furthermore, Internal Integration and Supplier Integration positively impact sustainability performance, whereas Customer Integration does not. Additionally, Internal Integration and Supplier Integration mediate the relationship between Digital Transformation and sustainability performance.